A Qualitative Investigation Into What Parents Want From an Online Behavioural Sleep Intervention for Children With Epilepsy - Cook, Georgia; Gringras, Paul; Hiscock, Harriet; Pal, Deb K.; Wiggs, Luci (Frontiers in Psychology, 2021)
Many of the same sleep problems seen in typically developing (TD) children are frequently experienced by children with epilepsy (CWE). Behavioural sleep interventions (BSIs) are commonly and successfully used to treat these sleep problems in TD children and in some neurodevelopmental disorder populations. Therefore, BSIs should be effective in CWE however, there are special seizure-related considerations for CWE and their parents which may be salient to consider in any future BSI development for this group. The current study sought to identify, from parents, if there were special considerations for the content and delivery of an online BSI for parents of CWE. Semi-structured interviews were conducted with 9 mothers of CWE and thematic analysis was conducted on the interview data. Ten themes were apparent which represented what parents wanted from any online BSI for CWE. Parents wanted i) other parents’ views and real-life experiences to be included, ii) recognition of how changes over time may influence the appropriateness of using various sleep-management options, iii) to be presented with a range of sleep management options from which they could select, iv) personalised information and suggestions for behaviour-change options, v) help to address child anxiety around sleep, vi) for the advice and behaviour-change options to be practical, vii) general educational information about sleep and the relationship between sleep and epilepsy, viii) for parental worries and concerns to be acknowledged, ix) to receive help, support and reassurance around children’s sleep; and x) to include the child in the intervention. It was clear that any online BSI would require specific adaptations and additions (to content and delivery format) to best meet the needs of parents of CWE. It is hoped that having identified what parents want from on online BSI for CWE will allow these factors to be acknowledged in future intervention development, with the intention to optimise parental engagement and intervention effectiveness. Practical suggestions for how these aspects could be integrated into any online BSI are suggested.